Reflection of the Hausa Society in Hausa Tales - Yusha’u, Nasiru (British Journal of Multidisciplinary and Advanced Studies, 2024)
Tales are to a certain extent the mirror of life, they reflect what people do, what they think, how they live and have lived, their values, their joys and their sorrows. The tales are also a means of articulating man’s response to his environment (Mbiti, 1966:31). In most traditional societies, tales served as one of the medium for understanding the societal mores and prescripts. The Hausa societies were not exceptional. In Hausa society, folktale is one of the ways of teaching societal values. It was/ is mostly presented by old women and young brides to teach children societal and moral ethics. This work aim at the study of the reflection of Hausa society in Hausa tales which critically analyses how tales depict the mode of life of the Hausa community. This covers the traditional and cultural set up which include marriage and family system, moral discipline and traditional political leadership system. The work traced some illustrations of tales relating to the above mentioned cultural norms of the Hausa society. The methods to be adopted in the research are the use of Anthology of tales of Yahaya and Usman in order to collect the data and analyses it. Structural functional approach and contextual method of translation are to be adopted as the theoretical framework. The recommendations include that the government should give emphasis on the teaching of folktales in the curriculum especially at the basic level of education.